Online course selection: using course dashboards to inform student enrollment decisions. (1st September 2016) - Marshall, James
Abstract: This article explores the potential of course dashboards as a front-end strategy for decreasing online course dropout rates. Scholarship has addressed course attrition once students are enrolled in online courses. However, supporting academic success by assisting students in the making of effective decisions about which online courses to take has received relatively little attention. Students in undergraduate-level online courses from varied disciplines rated the utility of course information types and three course dashboard prototypes. Qualitative feedback was also collected. Various types of information related to the time investment necessary to successfully complete the course were given priority. With regard to information displays, students preferred moderate-to-high amounts of well-organised information, presented with a careful balance of text and visual images. Comments from past students also favoured course dashboard elements.